Extraction and Characterization of Pepsin Soluble Collagen from the Body Wall of Sea Cucumber Acaudina leucoprocta. Issue 5 (28th May 2017) - Lin, Saijun; Xue, Ya-Ping; San, Enli; Keong, Tan Chee; Chen, Lifang; Zheng, Yu-Guo
ABSTRACT: Sea cucumber Acaudina leucoprocta is a potential alternative collagen source. However, the high levels of heavy metals contained in the body wall restricts its utilization. In this work, an efficient method was established to remove the heavy metals accumulated in the body wall of A.leucoprocta by demineralizing with 0.2 M ethylenediaminetetraacetic acid (EDTA). The resulting body wall of A.leucoprocta was then used for extracting pepsin-soluble collagen (PSC) with pepsin proteolysis. The PSC from the body wall of A.leucoprocta was obtained with a yield of 43.99 ± 0.65% (dry weight) and high purity. Maximum and minimum solubility for the isolated PSC in 0.5 M acetic acid was observed at pH 2.66 and 4.43, respectively. The solubility was remarkably decreased in the presence of NaCl. The denaturation temperature of PSC rehydrated in 0.5 M acetic acid was measured as 25.4°C. The PSC was characterized as type I collagen, which consists of three α1 chains without α2 chain. Interestingly, α1 chain in PSC showed two isoforms with the pI values of 4.02 and 4.29. The heavy metals existing in PSC were all below the contaminant limit of edible gelatin. The PSC isolated from the body wall could be an alternative to mammalian collagens.